Characterization of the relationship between lipids and volatile compounds in donkey, bovine, and sheep meat by UHPLC–ESI–MS and SPME–GC–MS. (1st February 2023) - Man, Limin; Ren, Wei; Qin, Huaxiu; Sun, Mengqi; Yuan, Shumao; Zhu, Mingxia; Liu, Guiqin; Wang, Changfa; Li, Mengmeng
Abstract: Lipids are the key substrates for volatile compound (VOC) formation; although meat lipid profiles vary across species, not much is known about differences in meat VOCs. Herein we analyzed and compared lipid and VOC profiles of donkey, bovine, and sheep meat by UHPLC–ESI–MS and SPME–GC–MS. In total, 1, 157 lipids belonging to 16 subclasses were identified [19.62% triglyceride (TG), 30.34% phosphatidylcholine, and 18.67% phosphatidylethanolamine]. Further, 97 differential lipids were screened, and three [e.g., PC(12:0/24:4), PC(O-18:2/20:5), and PC(O-18:2/22:6)] were identified as potential markers to distinguish between different meats. Thirteen characteristic VOCs were found, including heptanal, 1-octen-3-ol, ethyl acetate, and 1-hexanol, and there was a negative correlation with 21 screened phospholipid markers. To summarize, lipid and VOC profiles appear to be species dependent; moreover, differences in flavor are related to the profile of fatty acids in lipids. Our results should support future studies on meat aroma. Highlights: Phospholipids were the characteristic lipid in meat samples. Alkanes and alcohols were the predominant volatile compounds in meat samples. Phospholipids seem vital for generating volatile compounds. Lipids and volatile compounds in meat are species dependent.